SOCIODEMOGRAPHIC AND HEALTH RELATED CORRELATES OF PAST YEAR HELP SEEKING FOR ALCOHOL AND DRUG USE: DIFFERENCES BY AGE. (11th November 2018) - Sacco, P; Jun, H; Hochheimer, M; Kuerbis, A; Moore, A
Abstract: The prevalence of at-risk drinking, drug use, and substance use disorders has increased over the last decade and may continue to increase. Untreated substance use negatively impacts the health of middle-aged and older adults. Data from a national survey (NESARC-III) was used to quantify the prevalence of past-year help seeking stratified by age. An overall measure of help seeking was developed based on formal (e.g. detoxification) and informal (e.g. AA/NA) help seeking items for adults ages under 50 (n=21, 571) and 50+ (n=14, 738). Multiple group probit models assessed sociodemographic and health correlates of help seeking Past-year help seeking among those 50+ was lower for alcohol (<50:1.81%, ≥50:2.38%), drug use (<50:1.51% ≥50:0.75%) and combined (<50:4.24%, ≥50:3.30%%). Male gender (b=.24 p<.001), alcohol (b=.42; p<.001) and drug use (b=.71; p<.001) disorder, and major depression (b=.26; p<.001) were associated with greater probability of help seeking. Asian race (b=-.51; p<.001) and better mental health (b=-.02; p<.001) and physical health (b=-.004; p<.001) were associated with lower probability of help seeking. African-American/Black persons under 50 were less likely to seek help (b=-.25; p<.001); no differences were found among those 50+. Although a positive association was found between smoking and help seeking, the strength of the association was stronger (b=.55; p<.001) in those under 50 than over 50 (b=.28 z=4.43; p<.001). Help seeking rates were lower among older adults per previous literature. Few differences in correlates of use were found by age, but race disparities and smoking comorbidity should be explored further.